Analysis of Flavone C-Glycosides in the Leaves of Clinacanthus nutans (Burm. f.) Lindau by HPTLC and HPLC-UV/DAD - June Lee Chelyn; Maizatul Hasyima Omar; Nor Syaidatul Akmal Mohd Yousof; Ramesh Ranggasamy; Mohd Isa Wasiman; Zakiah Ismail (The Scientific World Journal)
Clinacanthus nutans (family Acanthaceae) has been used for the treatment of inflammation and herpes viral infection. Currently, there has not been any report on the qualitative and quantitative determination of the chemical markers in the leaves of C. nutans. The C-glycosidic flavones such as shaftoside, isoorientin, orientin, isovitexin, and vitexin have been found to be major flavonoids in the leaves of this plant. Therefore, we had developed a two-step method using thin-layer chromatography (TLC) and high pressure liquid chromatography (HPLC) for the rapid identification and quantification of the flavones C-glycosides in C. nutans leaves. The TLC separation of the chemical markers was achieved on silica gel 60 plate using ethyl acetate : formic acid : acetic acid : water (100 : 11 : 11 : 27 v/v/v/v) as the mobile phase. HPLC method was optimized and validated for the quantification of shaftoside, orientin, isovitexin, and vitexin and was shown to be linear in concentration range tested (0.4–200 μg/mL, r2 ≥ 0.996), precise (RSD ≤ 4.54%), and accurate (95–105%). The concentration of shaftoside, orientin, vitexin, and isovitexin in C. nutans leave samples was 2.55–17.43, 0.00–0.86, 0.00–2.01, and 0.00–0.91 mmol/g, respectively.